Effects of plyometric training on physical performance of young male soccer players: Potential effects of different drop jump heights - Ramirez-Campillo, R.; Alvarez, C.; Garcia-Pinillos, F.; Gentil, P.; Moran, J.; Pereira, L. A.; Loturco, I. (Pediatric Exercise Science, 2019)
Purpose: To compare the effects of plyometric drop jump (DJ) training against those induced by regular soccer training and assess the transference effect coefficient (TEC) of DJs ("trained exercises") performed from 20- (DJ20) and 40-cm (DJ40) height boxes with respect to different physical qualities (jumping, linear and change of direction speed, kicking, endurance, and maximal strength) in youth male soccer players. Methods: Participants were randomly divided into a control group (n = 20; age: 13.5 [1.9] y) and a DJ training group (n = 19; age: 13.2 [1.8] y), and trained for 7 weeks. A 2-way analysis of variance for repeated measures with the within-subject factor time (preintervention and postintervention) and between-subject factor group (intervention vs control) was performed. To calculate the TECs between the trained exercises (DJ20 and DJ40) and the physical tests, the ratio between the "result gains" (effect size [ES]) in the analyzed physical qualities and the result gains in the trained exercises were calculated. The TECs were only calculated for variables presenting an ES = 0.2. Results: Significant improvements (ES = 0.21-0.46; P < .05) were observed in the DJ training group, except in linear sprint performance. The control group improved only the maximal strength (ES = 0.28; P < .05). Significant differences were observed in all variables (ES = 0.20-0.55; P < .05) in favor of the DJ training group, except for maximal strength (group × time interaction). Conclusions: A plyometric training scheme based on DJs was able to significantly improve the physical performance of youth male soccer players. Overall, greater TECs were observed for DJ40 (0.58-1.28) than DJ20 (0.55-1.21).